Involvement of dynorphin and kappa opioid receptor in yohimbine-induced reinstatement of heroin seeking in rats - Zhou, Yan (2013)
Although kappa opioid receptor (KOP-r) antagonists are known to reduce reinstatement of cocaine, alcohol and nicotine seeking induced by a variety of stressors, the role of KOP-r in yohimbine-induced reinstatement of heroin seeking has not been investigated. Yohimbine, used as a stressor, increases the hypothalamic-pituitary-adrenal (HPA) hormones, causes anxiety and induces heroin craving in humans. The present experiments were undertaken to assess the effects of yohimbine on reinstatement of heroin seeking and associated changes in preprodynorphin (ppDyn) expression and HPA hormonal levels; and to determine whether these effects could be reduced by pretreatment with the selective KOP-r antagonist nor-binaltorphimine (nor-BNI). After heroin self-administration for 12 days (3h/day, 0.05 mg/kg/infusion, i.v.) and extinction for 8 days, reinstatement included the first baseline test after vehicle injection, the second test of yohimbine-induced reinstatement (1.25 mg/kg, i.p.), pretreatment with vehicle or nor-BNI (20 mg/kg, i.p.), the third baseline test after vehicle injection, and the final test of yohimbine-induced reinstatement. Immediately after the last test, several mesolimbic regions and plasma were collected for analyses of ppDyn and KOP-r mRNA levels and HPA hormones. Yohimbine-induced reinstatement was fully blocked by nor-BNI pretreatment. Furthermore, yohimbine elevated plasma HPA hormones, and this increase was blunted by nor-BNI. Finally, rats pre-treated with yohimbine displayed increased ppDyn mRNA levels in the nucleus accumbens shell and central nucleus of the amygdala. These data suggest that the stress responsive ppDyn/KOP-r system is a critical component of the neural circuitry underlying the effect of yohimbine stress on heroin seeking behavior and HPA activity.